RETRACTED: Economic aspect of unmanned open-pit coal mining technologies - Dubinkin D.M.; Golofastova N.N. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001